2022
DOI: 10.1186/s12871-022-01683-9
|View full text |Cite
|
Sign up to set email alerts
|

Propofol total intravenous anaesthesia versus inhalational anaesthesia for acute postoperative pain in patients with morphine patient-controlled analgesia: a large-scale retrospective study with covariate adjustment

Abstract: Background To compare the postoperative analgesic effect of propofol total intravenous anaesthesia (TIVA) versus inhalational anaesthesia (GAS) in patients using morphine patient-controlled analgesia (PCA). Methods A retrospective cohort study was performed in a single tertiary university hospital. Adult patients who used PCA morphine after general anaesthesia across 15 types of surgeries were included. Patients who received propofol TIVA were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The effect of different anesthetic techniques such as propofol-based total intravenous versus inhalational anesthesia seems to be very limited, although theoretically helpful through the antagonizing effect of propofol on the N-methyl-D-aspartate (NMDA) receptor and possibly preventive in certain study populations [6,103,132]. While certain effects seem to make sense in a pathophysiological way and single studies show some effects of pharmacological interventions, a currently updated meta-analysis shows the disappointing fact that overall, the effects of most drugs (e.g.…”
Section: Risk Factors Related To Surgical Procedures and Pain Managementmentioning
confidence: 99%
“…The effect of different anesthetic techniques such as propofol-based total intravenous versus inhalational anesthesia seems to be very limited, although theoretically helpful through the antagonizing effect of propofol on the N-methyl-D-aspartate (NMDA) receptor and possibly preventive in certain study populations [6,103,132]. While certain effects seem to make sense in a pathophysiological way and single studies show some effects of pharmacological interventions, a currently updated meta-analysis shows the disappointing fact that overall, the effects of most drugs (e.g.…”
Section: Risk Factors Related To Surgical Procedures and Pain Managementmentioning
confidence: 99%
“…Some clinical studies have also suggested that propofol TIVA is associated with a reduction in postoperative pain [ 27 , 28 ]. A subgroup analysis in a recent retrospective cohort study found that propofol TIVA was associated with a clinically significant reduction in postoperative pain scores and opioid consumption in patients undergoing hepatobiliary and pancreatic surgery [ 29 ]. Another retrospective study found that propofol TIVA was associated with less pain during coughing and reduced morphine consumption in patients undergoing liver surgery [ 30 ].…”
Section: Potential Advantages Of Tiva For Hepatic Resectionmentioning
confidence: 99%
“…Five clinical trials did not show a significant difference. 13 The use of bilateral tranversus abdominis plane block for abdominoplasty was associated with a longer postoperative analgesia duration in the last 24 hours and lower morphine consumption in the first 24 hours than other surgically infiltrated anesthetic techniques. 14 Liposomal bupivacaine (Exparel) was introduced as a safe method and an alternative to invasive postoperative pain management options such as PCA, epidurals, peripheral nerve catheters, or intravenous narcotics.…”
Section: Introductionmentioning
confidence: 97%